2009
DOI: 10.21608/jfds.2009.115354
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Using Seed Coats on Hypoglycemic in Rats

Abstract: Celluloses fiber substances were prepared from wheat and hull less barley bran. Sodium hydroxide solution was used and the precipitate was centrifuged and washed by water several time to remove the color in first stage followed by peroxidation in the second stage. The products were washed to pH 6.0 + 0.5 and dried using warm air in an electric oven. The chemical and physical properties of the raw materials and celluloses fiber from all bran are characterized. The results showed that the highest cellulose and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…However, Hussein et al 18 extended this by examining mineral content, corroborating the increase in ash content seen in our study with FE and FT supplements. Also, Studies by Yousef et al 20 and Sandak et al 22 showed that unconventional additives like red algae and seed coats can also alter the bread's chemical composition.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Hussein et al 18 extended this by examining mineral content, corroborating the increase in ash content seen in our study with FE and FT supplements. Also, Studies by Yousef et al 20 and Sandak et al 22 showed that unconventional additives like red algae and seed coats can also alter the bread's chemical composition.…”
Section: Resultsmentioning
confidence: 99%
“…The enrichment of red algae was studied by Yousef et al 20 , while Hussein et al 21 assessed low-protein variants. Ingredients like seed coats, rice bran, and watermelon rinds were experimented with to assess changes in chemical and sensory properties, as well as potential health benefits 22 25 . Also, the color attributes of Baladi bread can be altered by ingredients and processing techniques.…”
Section: Introductionmentioning
confidence: 99%